2013
DOI: 10.4238/2012.april.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent expression of the BPI gene in Sutai piglets

Abstract: ABSTRACT. We compared and analyzed expression of the BPI gene of Sutai piglets ranging from newborn to post-weaning days 8, 18, 30, and 35 by the real-time PCR method, in order to determine if it is involved in protection against disease caused by ETEC F18. There was a significant difference between 18-and 35-day expression in the jejunum. There were also significant differences between 35-day expression and expression at the other development stages in the duodenum. There were no significant differences in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A similar situation has been observed in vitro for ETEC, with LT expression modified by pH [ 52 ]. Also, it has been demonstrated that the porcine intestinal epithelium can develop a resistance to F18-mediated adherence [ 53 ] and the stress of early weaning reduces the ability of piglets to cope with ETEC infection [ 54 ]. This data indicates that whilst it is important to characterise pathogenic E. coli , host characteristics and the intestinal environment may play a role in altering pathogenicity and account for the variation in disease severity between these isolates given their highly similar virulence factor content.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation has been observed in vitro for ETEC, with LT expression modified by pH [ 52 ]. Also, it has been demonstrated that the porcine intestinal epithelium can develop a resistance to F18-mediated adherence [ 53 ] and the stress of early weaning reduces the ability of piglets to cope with ETEC infection [ 54 ]. This data indicates that whilst it is important to characterise pathogenic E. coli , host characteristics and the intestinal environment may play a role in altering pathogenicity and account for the variation in disease severity between these isolates given their highly similar virulence factor content.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli F18 is the primary causative of diarrhea and edematous disease which are two major causes of mortality in postweaning piglets, and these disease lead to huge economic losses in the swine industry [6]. Our preliminary study suggested that BPI expression is connected to resistance against E. coli F18 [7]. …”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that expression of the BPI gene in the duodenum and jejunum of Sutai piglets was significantly higher than that in Yorkshire and Meishan piglets. In a previous study, we analyzed BPI gene expression in Sutai piglets over a time period ranging from newborns to post-weaning days 8, 18, 30, and 35 (Zhu et al, 2013). There were significant differences between 35-day expression and expression at other developmental stages in the duodenum, with the greatest vulnerability to E. coli F18 infection detected at 35 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of BPI between enterotoxigenic E. coli F18 (ETEC F18)-resistant and ETEC F18-sensitive piglets was analyzed in our preliminary study, and we determined that expression of BPI is significantly high only in the duodenum and jejunum of pigs, suggesting that increased expression of BPI in the intestines is related to the resistance to ETEC F18 (Ye et al, 2011). Moreover, Zhu et al (2013) observed significant differences between 35-day expression and expression during other development stages in the duodenum by analyzing the age-dependent tissue expression of porcine BPI in Sutai pigs (Zhu et al, 2013). The greatest susceptibility to E. coli F18 infection was observed at 35 days of age, with predominant E. coli F18 colonization in the duodenum.…”
Section: Introductionmentioning
confidence: 99%